Learn psychology - Carter, Kenneth 1967-.; Seifert, Colleen M.; Kwiatkowski, Jonna (Burlington, MA Jones & Bartlett Learning, 2018)
"Learn Psychology supplies the fundamental text for introduction to psychology courses centered on 21st century learners. This comprehensive textbook presents introductory psychology in a format that is highly interactive, compatible with digital applications, and easy to use. Fully cognizant of today's economic challenges, Learn Psychology prepares students for the modern workforce with practical applications of core concepts in psychology: a 'learning by doing' approach that pairs critical analysis of the psychological topics with examples form everyday life. Psychology is the science of behavior and mental processes, and the biological, experiential, and sociocultural factors that influence behavior. Learn Psychology highlights the multiple influences that affect psychological phenomena. Each chapter explains a given topic through the lens of the multiple influences on psychology. Psychological science and the methods involved in both classic and state-of-the-art research are presented throughout."--Provided by publisher.
Psychology : an overview -- A scientific approach to psychology -- Neuroscience : the biology of behavior -- Sensation and perception -- States of consciousness -- Learning -- Memory -- Thinking and language -- Intelligence -- Motivation -- Emotion, stress, and health -- Development throughout the lifespan -- Personality -- Psychological disorders -- Therapies for psychological disorders -- Social psychology.
Includes bibliographical references and index.
Keywords: Psychology